A control strategy of converters based on constant extinction area for UHVDC system under hierarchical connection. (September 2021) - Han, Pingping; Sun, Haoran; Tong, Qingyang; Zhang, Yan; Chen, Zhong; Yang, Wei; Yang, Xiangzhen
Highlights: A coordinated control strategy of the converter based on the constant cut-off area; Commutation area theory and the coupling mechanism of the system; Improvement of transient characteristics of UHVDC system. Abstract: The Ultra High Voltage Direct Current (UHVDC) systems under hierarchical connection, while improving the voltage support and current assimilative capacity of the receiving-end system, also bring new challenges to the security and stability of the power grid. An AC short-circuit fault at the receiving-end system can easily induce commutation failures (CFs) of the high-end and low-end converter at the same time, which seriously affects the stability of the system. Therefore, it is urgent to study the coordinated control strategy for the commutation failures of UHVDC systems under hierarchical connection. This paper analyzes the coupling mechanism and CFs characteristics of the high-end and low-end converters of a UHVDC system under hierarchical connection. Based on the commutation area theory of the three-phase full-wave bridge circuit, a coordinated control strategy is proposed to suppress CFs of the non-faulty layer converter of the UHVDC system under hierarchical connection. It can reserve enough extinction area for the non-faulty layer converter after an AC system failure occurs, thus preventing the occurrence of commutation failure. Finally, based on PSCAD/EMTDC, Zhundong-Wannan ±1100 kV UHVDC was built and the effectiveness of the proposed control strategy was simulated and verified. The simulation results show that the proposed control strategy can effectively suppress the simultaneous commutation failure of inverter station converters when symmetrical faults and asymmetrical faults of different levels occur in the receiving-end grid. This has important engineering significance for improving the stability of the DC transmission system.